The cost-effectiveness of temporary single-patient rooms to reduce risks of healthcare-associated infection. (October 2021) - Graves, N.; Mitchell, B.G.; Otter, J.A.; Kiernan, M.
Summary: Background: The use of single rooms for patient isolation often forms part of a wider bundle to prevent certain healthcare-associated infections (HAIs) in hospitals. Demand for single rooms often exceeds what is available and the use of temporary isolation rooms may help resolve this. Changes to infection prevention practice should be supported by evidence showing that cost-effectiveness is plausible and likely. Aim: To perform a cost-effectiveness evaluation of adopting temporary single rooms into UK National Health Service (NHS) hospitals. Methods: The cost-effectiveness of a decision to adopt a temporary, single-patient, isolation room to the current infection prevention efforts of an NHS hospital was modelled. Primary outcomes are the expected change to total costs and life-years from an NHS perspective. Findings: The mean expected incremental cost per life-year gained (LYG) is £5, 829. The probability that adoption is cost-effective against a £20, 000 threshold per additional LYG is 93%, and for a £13, 000 threshold the probability is 87%. The conclusions are robust to scenarios for key model parameters. If a temporary single-patient isolation room reduces risks of HAI by 16.5% then an adoption decision is more likely to be cost-effective than not. Our estimate of the effectiveness reflects guidelines and reasonable assumptions and the theoretical rationale is strong. Conclusion: Despite uncertainties about the effectiveness of temporary isolation rooms for reducing risks of HAI, there is some evidence that an adoption decision is likely to be cost-effective for the NHS setting. Prospective studies will be useful to reduce this source of uncertainty.